Grooming-Related Concerns Among Companion Animals: Preliminary Data on an Overlooked Topic and Considerations for Animals' Access to Health-Related Services - McDonald, Shelby E.; Sweeney, Jessica; Niestat, Laura; Doherty, Colleen (Frontiers in Veterinary Science, 2022)
Grooming is an essential health maintenance activity that is fundamental to the welfare of many companion animals. Despite the potentially serious consequences of inadequate grooming for pets and their caregivers, few studies have examined the role of access to pet grooming services and supplies in promoting and maintaining companion animal health and welfare. The goal of this paper was two-fold: 1) To provide preliminary findings demonstrating the scope of grooming and matting concerns among animals served by a large, non-profit animal welfare organization and 2) to provide a call for research to guide effective prevention of and responses to grooming-related omissions of care. We retrospectively extracted data from five American Society for the Prevention of Cruelty to Animals (ASPCA) programs serving the New York City area: ASPCA Animal Hospital (AAH), Community Medicine (CM), One ASPCA Fund, ASPCA-NYPD (New York City Police Department) Partnership, and the Community Engagement (CE) Program. The prevalence of grooming–related concerns was relatively consistent across all three veterinary service programs (AAH: 6%; CM: 4%; One ASPCA Fund: 6%). Thirteen percent of the ASPCA-NYPD Partnership’s cruelty cases involved general hair matting concerns and/or strangulating hair mat wounds (93% were long-haired dog breed types). Five percent of CE cases received grooming-related supplies to support pet caregivers’ in-home grooming capabilities. Our findings underscore the need to understand the scope of grooming-related concerns among animals served by veterinarians and other community programs to improve animals’ access to health-related services.